Ti3C2Tx nanosheet / self-assembled tetra (4-carboxyphenyl) porphyrin composite catalyst as well as preparation method and application thereof
Through the use of Ti3C2Tx nanosheets and SA-TCPP composite catalyst, the problem of insufficient H2O2 generation and organic pollutant degradation efficiency in existing photocatalytic-self-Fenton technology is solved, and efficient photocatalytic production of H2O2 and self-Fenton degradation is achieved. The effect has improved the efficiency of water treatment and resource utilization.
Patent Information
- Application Number
- CN202411443319.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing photocatalytic-self-fenton technology has shortcomings in the efficiency of H2O2 generation and organic pollutant degradation, especially the π-π accumulation of SA-TCPP leads to low photocatalytic activity, high external heating demand, large resource consumption and improved efficiency limited.
The catalyst was prepared by composited Ti3C2Tx nanosheets with self-assembled tetracarbazine (4-carboxyphenyl)porphyrin (SA-TCPP), and synthesized by in-situ self-assembly method, using the photothermal conversion ability and conductivity of Ti3C2Tx to improve the photocatalytic efficiency, and The iron salt triggers the Fenton reaction, and generates a large number of hydroxyl radicals for degradation of organic pollutants.
The performance of photocatalytic H2O2 production and self-fenton degradation efficiency have been significantly improved. The H2O2 generation rate reaches 247.3μmol·g-1·h-1, which is 11 times that of pure SA-TCPP, and is 2,4-dichlorochloride within 100 minutes. The removal rate of phenol increased from 21.5% to 99.7% and had good reusability.
Smart Images

Figure CN119456047A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite catalysts, and in particular to a Ti3C2T x Nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst and preparation method and application thereof. Background Art
[0003] At present, the main treatment methods for removing organic pollutants include physical methods, biological methods and advanced oxidation methods. As an outstanding representative of advanced oxidation technology, Fenton technology can degrade organic pollutants indiscriminately and has become a research hotspot in the field of water treatment. However, there are problems such as large demand for H2O2 and low effective utilization rate, which limits the wider application of Fenton technology. As an emerging solution, photocatalytic-self-Fenton technology generates H2O2 in situ through photocatalysis and combines it with Fenton technology, which solves the supply problem of H2O2 and enhances the durability of Fenton technology, achieving efficient and sustainable degradation of organic matter. Therefore, the development of new and efficient photocatalytic-self-Fenton technology is of great significance in the field of water treatment.
[0004] Self-assembled tetrakis(4-carboxyphenyl)porphyrin (SA-TCPP) is a new type of organic photocatalytic material. It has been widely studied for its good chemical stability, visible light activity and structural diversity. However, its particle size is small and π-π stacking is prone to occur, resulting in problems such as high recombination rate of photogenerated carriers and few reaction sites, resulting in low photocatalytic activity. The current technical level prepares catalysts by combining graphene oxide with SA-TCPP for photocatalytic-self-Fenton water treatment technology. However, this technology requires external heating during the reaction process to promote SA-TCPP to produce H2O2. This high temperature requirement not only consumes a lot of resources, but also has limited efficiency improvement, which only increases by 1.78 times, resulting in the subsequent pollutant degradation effect is not significant. Therefore, it is of great significance to appropriately modify SA-TCPP to improve the photocatalytic H2O2 production activity so that it conforms to the construction of the photocatalytic-self-Fenton system. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a Ti3C2T x Nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst and its preparation method and application, Ti3C2T x It has excellent photothermal conversion capability and can be used as a photothermal medium to improve photocatalytic efficiency. In addition, its excellent conductivity helps accelerate the migration of photogenerated carriers, and the Ti sites on its surface provide strong redox capabilities.
[0006] The above object of the present invention is achieved through the following technical solutions:
[0007] The first aspect of the present invention provides a Ti3C2T x The preparation method of the nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst comprises the following steps:
[0008] (1) dissolving tetrakis(4-carboxyphenyl)porphyrin (TCPP) in an alkaline solution, and then adding an acid solution to adjust the pH value to neutral to obtain a self-assembled tetrakis(4-carboxyphenyl)porphyrin (SA-TCPP) dispersion;
[0009] (2) mixing the self-assembled tetrakis(4-carboxyphenyl)porphyrin dispersion and Ti3C2T x The dispersions are mixed to obtain the Ti3C2T x Nanosheets / Self-assembled Tetrakis(4-carboxyphenyl)porphyrin (Ti3C2T x / SA-TCPP) composite catalyst.
[0010] The present invention synthesizes Ti3C2T by in-situ self-assembly method x / SA-TCPP composite catalyst has excellent photocatalytic H2O2 production performance under light source irradiation.
[0011] Furthermore, in step (1), the mass ratio of the TCPP to the volume of the alkaline solution is (50-100) mg:(1.79-5) mL.
[0012] Furthermore, in step (1), the concentration of the alkali in the alkali solution is 1-2M.
[0013] Furthermore, in step (1), the concentration of the acid in the acid solution is 0.1-0.2M.
[0014] Furthermore, in step (2), the Ti3C2T x Ti3C2T in dispersion x The concentration of the nanosheets is 2-8 mg / mL, preferably 4-8 mg / mL, and more preferably 4-6 mg / mL.
[0015] Furthermore, in step (2), the Ti3C2T x The nanosheets are prepared by the following method: adding Ti3AlC2 to a mixed solution of hydrochloric acid and lithium fluoride to perform an etching reaction, washing the supernatant after the reaction to a neutral pH value, and then subjecting the Ti3C2T2 to ultrasonic stripping, centrifugation, and drying. x (T x Including -O, -F, -OH, etc.) nanosheets.
[0016] Furthermore, the concentration of hydrochloric acid in the mixed solution of hydrochloric acid and lithium fluoride is 9-10M.
[0017] Furthermore, the concentration of lithium fluoride in the mixed solution of hydrochloric acid and lithium fluoride is 70-80 mg / mL.
[0018] Furthermore, the etching reaction temperature is 40-45° C. and the time is 36-48 hours.
[0019] Furthermore, the ultrasonic peeling is performed under the following conditions: ultrasonication at a power of 400-500 W for 1-2 h.
[0020] Furthermore, the tetrakis(4-carboxyphenyl)porphyrin described in step (1) and the Ti3C2T x The mass ratio of nanosheets is 1:(0.2-0.8).
[0021] Furthermore, in step (2), the self-assembled tetrakis(4-carboxyphenyl)porphyrin dispersion and Ti3C2T x The volume ratio of the dispersion is (2-10):1.
[0022] Furthermore, in step (2), the specific operation of the mixing is: ultrasonication at a power of 400-500 W for 1-2 h, and then stirring at 40-50° C. for 2-3 h.
[0023] Furthermore, in step (2), the mixing further includes washing and drying steps.
[0024] The second aspect of the present invention provides Ti3C2T obtained by the preparation method described in the first aspect. x Nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst.
[0025] The third aspect of the present invention provides the Ti3C2T x Application of nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst in photocatalytic-self-Fenton water treatment.
[0026] Furthermore, the photocatalytic-self-Fenton water treatment method comprises the following steps: adding Ti3C2T x The nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst was added with iron salt to construct a photocatalytic-self-Fenton system, which was then placed under a light source for irradiation and continuous ventilation to keep the solution in an oxygen-saturated state.
[0027] The Ti3C2T provided by the present invention xThe nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst has efficient photocatalytic H2O2 production performance. By adding an appropriate amount of iron salt into the reaction system to initiate the self-Fenton reaction, a large number of hydroxyl radicals (·OH) are generated as the main active substance. The active substances (such as superoxide anion radicals, holes, etc.) generated during the reaction act synergistically, thereby efficiently degrading organic pollutants.
[0028] Furthermore, the organic pollutant is selected from one or more of 2,4-dichlorophenol, phenol (Phenol), bisphenol F (BPF) and carbamazepine (CBZ).
[0029] Furthermore, the Ti3C2T x The volume ratio of the mass of the nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst to the solution containing organic pollutants is 1 mg:(3-7) mL.
[0030] Furthermore, the Ti3C2T x The mass ratio of the nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst to the iron salt is 1:(0.2-0.6).
[0031] Furthermore, Ti3C2T x The nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst is then subjected to ultrasonic treatment at a power of 400-500 W for 1-2 h.
[0032] Furthermore, after the ultrasonic treatment, the reaction system is stirred to reach adsorption-desorption equilibrium.
[0033] Furthermore, the iron salt is ferric sulfate (Fe2(SO4)3) and / or ferrous sulfate (FeSO4).
[0034] Furthermore, the pH value of the photocatalytic-self-Fenton system is 3-8.5, preferably 3-6.5.
[0035] Furthermore, before adding the iron salt, the pH value of the reaction system is adjusted to 3-8.5 using dilute hydrochloric acid or hydrogen peroxide solution.
[0036] Furthermore, the wavelength of the light source is 200-1300 nm, preferably 420-800 nm.
[0037] Furthermore, the light source is sunlight or an artificial light source, and the artificial light source can be a xenon lamp, an LED lamp, an ultraviolet lamp, a laser, a high-pressure mercury lamp, etc.
[0038] Furthermore, the ventilation mainly refers to the introduction of oxygen.
[0039] Beneficial effects of the present invention:
[0040] The present invention constructs a new Ti3C2T by self-assembly method x / SA-TCPP composite catalyst, Ti3C2T x The introduction of Ti3C2T not only improves the light absorption capacity, but also enhances the efficient separation and mobility of photogenerated carriers, thereby significantly improving the photocatalytic H2O2 production performance and self-Fenton degradation efficiency. x The H2O2 generation rate of the / SA-TCPP composite catalyst can reach 247.3 μmol·g under visible light irradiation and without sacrificial agent. -1 ·h -1 , which is 11 times that of pure SA-TCPP.
[0041] The Ti3C2T x The photocatalytic-self-Fenton system of the SA-TCPP composite catalyst increased the removal efficiency of 2,4-dichlorophenol from 21.5% to 99.7% within 100 minutes. The system also has good reusability and applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x Zeta potential diagram of / SA-TCPP composite catalyst.
[0043] Figure 2 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x DRS pattern of / SA-TCPP composite catalyst.
[0044] Figure 3 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x XPS graph of / SA-TCPP composite catalyst; among them, (A) is the full spectrum, (B) is the Ti 2p spectrum, (C) is the C1s spectrum, and (D) is the O1s spectrum.
[0045] Figure 4 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x TEM image of the Ti3C2T / SA-TCPP composite catalyst; (A) is Ti3C2T x Nanosheets, (B) SA-TCPP, (C) Ti3C2T x / SA-TCPP composite catalyst.
[0046] Figure 5 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x Photoelectric performance diagram of SA-TCPP composite catalyst; (A) is the PL spectrum diagram, and (B) is the TCP curve diagram of alternating light and dark.
[0047] Figure 6 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Examples 1-4 x FT-IR graph of / SA-TCPP composite catalyst.
[0048] Figure 7 These are the test result graphs of Test Examples 1-4; wherein, (A) is the test result graph of the photocatalytic H2O2 production performance of Test Example 1, (B) is the test result graph of the photocatalytic-self-Fenton reaction of Test Example 2 under different pH values, (C) is the test result graph of the photocatalytic-self-Fenton reaction of Test Example 3 under different iron salt types, and (D) is the test result graph of the photocatalytic-self-Fenton reaction of Test Example 4 under different iron salt contents.
[0049] Figure 8 For test example 5, the Ti3C2T x Mechanism diagram of SA-TCPP composite catalyst for photocatalytic-self-Fenton water treatment.
[0050] Fig. 9 The test result diagrams of Test Example 5 and Test Example 6; wherein (A) is a degradation activity curve diagram, and (B) is a data diagram of the apparent rate constant.
[0051] Fig.10 The test result diagrams of Test Example 5 and Test Example 7; wherein (A) is a degradation activity curve diagram, and (B) is a data diagram of the apparent rate constant.
[0052] Fig.11 For test example 8, the Ti3C2T x / SA-TCPP composite catalyst is used for photocatalysis-Fenton water treatment to compare the degradation performance of 2,4-dichlorophenol after adding different active species capture agents.
[0053] Fig.12 For Test Example 9, the Ti3C2T x / SA-TCPP composite catalyst for photocatalytic-self-Fenton water treatment cyclic degradation activity diagram. DETAILED DESCRIPTION
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0055] In the following examples, Ti3C2T x The nanosheets were prepared by the following method: 1.6 g of LiF was placed in a 100 mL polytetrafluoroethylene beaker, and 20 mL of 9 M HCl was added. The mixed solution was placed in a constant temperature magnetic stirrer at 40 ° C and stirred at a certain speed for 30 minutes until the LiF was completely dissolved. Then 1 g of Ti3AlC2 was slowly added to the solution and allowed to react for 48 hours. After the reaction, the solution was repeatedly washed by centrifugation and deionized water until the pH value of the solution was higher than 5. After washing, it was subjected to 1 hour of ultrasonic treatment. Finally, it was centrifuged and placed at 60 ° C for vacuum drying overnight to obtain Ti3C2T x Nanosheets.
[0056] In the following examples, SA-TCPP was prepared by the following method: 100 mg of TCPP was dissolved in 3.58 mL of KOH (1 M) solution, heated and stirred in a 50° C. water bath for 30 min until the solid was completely dissolved; then 0.1 M HCl solution was quickly added until the pH value of the solution was close to neutral, the mixed solution was allowed to stand, naturally cooled, centrifuged, washed with ultrapure water several times, and vacuum dried at 60° C. overnight to obtain SA-TCPP.
[0057] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0058] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0059] Example 1
[0060] A Ti3C2T x Nanosheets / Self-assembled Tetrakis(4-carboxyphenyl)porphyrin (Ti3C2T x The preparation method of the composite catalyst comprises the following steps:
[0061] (1) Dissolve 100 mg of TCPP in 3.58 mL of KOH (1 M) solution and heat in a 50 °C water bath with stirring for 30 min until the solid is completely dissolved; then quickly add 32.22 mL of 0.1 M HCl solution until the pH value of the solution is close to neutral, and then stir for 30 min to obtain a SA-TCPP dispersion.
[0062] (2) The 35.8 mL SA-TCPP dispersion and 10 mL Ti3C2T x Dispersion mixing, Ti3C2T x Ti3C2T in dispersion x The concentration of the nanosheets was 6 mg / mL, and the mixture was ultrasonicated for 1 h, and then heated and stirred at 50 °C for 3 h. Finally, the mixture was vacuum dried at 60 °C overnight to obtain the Ti3C2T x / SA-TCPP composite catalyst.
[0063] Figure 1 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x Zeta potential diagram of / SA-TCPP composite catalyst, such as Figure 1 As shown, Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T x The Zeta potentials of the Ti3C2T4 / SA-TCPP composite catalysts were -12.29 mV, -11.23 mV, and -15.84 mV, respectively. x / SA-TCPP composite catalysts are not held together by simple electrostatic attraction.
[0064] Figure 2 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x / SA-TCPP composite catalyst diffuse reflectance spectrum (DRS) diagram, such as Figure 2 As shown in the figure, SA-TCPP has a strong light-harvesting ability in the visible light region, with a strong absorption peak at about 372 nm and four weak absorption peaks at 520 nm, 558 nm, 594 nm and 650 nm, corresponding to the Soret (B) band and four Q bands of porphyrin, respectively. x It exhibits strong light absorption in the entire wavelength range (200-1000nm), and due to its metallic nature, it does not show a clear absorption edge. xThe Ti3C2T / SA-TCPP composite catalyst exhibits stronger light absorption capacity and range than SA-TCPP. It not only has visible light response, but also has much higher light absorption capacity in the near-infrared region than Ti3C2T x In addition, the Soret (B) band in the composite catalyst was red-shifted compared with that in SA-TCPP, which further proves that Ti3C2T x The introduction of promotes the π-π stacking of SA-TCPP. x / SA-TCPP composite catalyst forms a large-scale electron delocalization and also promotes the effective separation of photogenerated carriers.
[0065] Figure 3 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x X-ray photoelectron spectroscopy (XPS) of the SA-TCPP composite catalyst; (A) is the full spectrum, (B) is the Ti2p spectrum, (C) is the C1s spectrum, and (D) is the O1s spectrum. Figure 3 As shown in (A), Ti3C2T x There are five element peak signals of C, O, N, F and Ti in the / SA-TCPP composite catalyst. Figure 3 As shown in (B), Ti3C2T x The Ti spectrum can be divided into six peaks at 455.4eV, 456.7eV, 459.3eV, 461.6eV, 462.3eV and 465.3eV, corresponding to Ti(II)2p 3 / 2 、Ti(III)2p 3 / 2 、Ti(IV)2p 3 / 2 、Ti(II)2p 1 / 2 、Ti(III)2p 1 / 2 and Ti(IV)2p 1 / 2 Due to Ti3C2T x The high reducibility of Ti ions makes it possible for low-valent Ti ions to act as electron donors to reduce Fe(III) and activate molecular oxygen during the catalytic process. Figure 3 As shown in (C), Ti3C2T x The C1s spectrum of the prepared Ti3C2T4O ... xThe surface ends of the nanosheets are modified by -OH. The C1s spectrum of SA-TCPP shows peaks at 284.8 eV, 285.5 eV, and 288.8 eV, which are attributed to sp2 carbon atoms CC, CN, and O=CO, respectively. Ti3C2T x The C1s spectrum of the / SA-TCPP composite catalyst can be divided into four peaks, which are from SA-TCPP and Ti3C2T x sp2 hybridized carbon atoms C-Ti-O (282.3 eV), CC (284.8 eV), CO (286.3 eV) and O=CO (288.7 eV). Figure 3 As shown in (D), SA-TCPP has three peaks at 531.7 eV, 533.4 eV, and 534.7 eV, which are attributed to C=O, O in adsorbed H2O, and O in aromatic C-OH, respectively; Ti3C2T x The peaks at 530.2eV, 531.8eV, and 533.1eV are attributed to TiO2, C-Ti-O, and O adsorbed from H2O; Ti3C2T x The SA-TCPP composite catalyst has four peaks at 530.2eV, 531.6eV, and 533.0eV, which are respectively attributed to TiO2, C=O, and O adsorbed in H2O. x The C=O bond in the / SA-TCPP composite catalyst shifts 0.1 eV toward a lower binding energy, which is due to the Ti3C2T x There is a π-π interaction force between SA-TCPP, which increases the electronic state density.
[0066] Figure 4 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x / SA-TCPP composite catalyst transmission electron microscope (TEM) image; where (A) is Ti3C2T x Nanosheets, (B) SA-TCPP, (C) Ti3C2T x / SA-TCPP composite catalyst. Figure 4 As shown in (A), Ti3C2T x Nanosheets present a two-dimensional sheet structure. Figure 4 As shown in (B), SA-TCPP is a small-sized nanocrystal with a diameter of about 5 nm. Figure 4 Compared with (A), Figure 4 The surface of (C) is rough, and a large amount of SA-TCPP is evenly distributed on the Ti3C2T xThe surface of the nanosheets is beneficial to increase the active sites. In summary, SA-TCPP successfully attached to the Ti3C2T x Nanosheet surface, successfully prepared Ti3C2T x / SA-TCPP composite catalyst.
[0067] Figure 5 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x Photoelectric performance diagram of SA-TCPP composite catalyst; (A) is the photoluminescence (PL) spectrum diagram, (B) is the photocurrent response value (TCP) curve diagram of light-dark alternation. Figure 5 As shown, Ti3C2T x The fluorescence signal of the SA-TCPP composite catalyst was significantly reduced, while the photocurrent response value (TCP) was significantly increased, indicating that the separation efficiency of photogenerated carriers was significantly improved.
[0068] Example 2
[0069] A Ti3C2T x The preparation method of the / SA-TCPP composite catalyst is basically the same as that of Example 1, except that: in step (2), Ti3C2T x Ti3C2T in dispersion x The concentration of nanosheets was 2 mg / mL.
[0070] Example 3
[0071] A Ti3C2T x The preparation method of the / SA-TCPP composite catalyst is basically the same as that of Example 1, except that: in step (2), Ti3C2T x Ti3C2T in dispersion x The concentration of nanosheets was 4 mg / mL.
[0072] Example 4
[0073] A Ti3C2T x The preparation method of the / SA-TCPP composite catalyst is basically the same as that of Example 1, except that: in step (2), Ti3C2T x Ti3C2T in dispersion x The concentration of nanosheets was 8 mg / mL.
[0074] Figure 6 Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Examples 1-4 x / SA-TCPP composite catalyst Fourier transform infrared spectrum (FT-IR) diagram, such as Figure 6 As shown, compared with pure SA-TCPP, Ti3C2T x / SA-TCPP composite catalyst at 1600cm -1 The C=C stretching vibration peak near the Ti3C2T x There is a π-π stacking interaction between the nanosheets and SA-TCPP.
[0075] Test Example 1
[0076] Photocatalyst Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Examples 1-4 x / SA-TCPP composite catalyst was used to test the photocatalytic H2O2 production performance. The test method was as follows:
[0077] First, add 50mL of deionized water and 10mg of photocatalyst to a quartz reactor, ultrasonicate the reaction solution for 30min, and then stir it for 30min in the dark to reach adsorption-desorption equilibrium. Subsequently, the reaction system was irradiated under visible light for 1h, and oxygen was continuously introduced during the reaction. During the reaction, 1mL of potassium hydrogen phthalate solution (0.1M) and 1mL of potassium iodide solution (0.4M) were mixed with the above reaction solution at regular intervals, and then the mixed solution was shaken at 37°C in the dark for 1h. The absorbance value at 350nm was measured to estimate the H2O2 concentration. The test results are as follows: Figure 7 As shown in (A).
[0078] Test Example 2
[0079] 10 mg of Ti3C2T prepared in Example 1 was added x / SA-TCPP composite catalyst was added to 50mL 2,4-dichlorophenol solution (10mg / L) and stirred in the dark for 20min. The pH value of the system was adjusted to 3, 5, and 6.5 with dilute hydrochloric acid, and the pH value of the system was adjusted to 8.5 with dilute sodium hydroxide solution. Then 4mg Fe2(SO4)3 was added to the reaction system to initiate the self-Fenton reaction. The system was exposed to visible light and oxygen was continuously introduced during the reaction. 2mL of samples were taken every 20min, centrifuged and filtered through a 0.22μm water filter. After removing the composite catalyst, it was used for liquid phase testing to test the effect of different pH values on the photocatalytic-self-Fenton reaction. The test results are shown in Figure 7 As shown in (B).
[0080] Test Example 3
[0081] 10 mg of Ti3C2T prepared in Example 1 was added x / SA-TCPP composite catalyst was added to 50mL 2,4-dichlorophenol solution (10mg / L) and stirred in the dark for 20min. Then 4mg of Fe2(SO4)3 or FeSO4 was added to the reaction system (pH value was about 5) to initiate the self-Fenton reaction, and the reaction system was exposed to visible light. Oxygen was continuously introduced during the reaction. 2mL was sampled every 20min, centrifuged and filtered through a 0.22μm water filter. After removing the composite catalyst, it was used for liquid phase testing to test the effects of different iron salt types on the photocatalytic-self-Fenton reaction. The test results are shown in Figure 7 As shown in (C).
[0082] Test Example 4
[0083] 10 mg of Ti3C2T prepared in Example 1 was added x / SA-TCPP composite catalyst was added to 50mL 2,4-dichlorophenol solution (10mg / L) and stirred in the dark for 20min. Then 2mg, 4mg, and 6mg Fe2(SO4)3 were added to the reaction system (pH value was about 5) to initiate the self-Fenton reaction. The reaction system was exposed to visible light and oxygen was continuously introduced during the reaction. 2mL of samples were taken every 20min, centrifuged and filtered through a 0.22μm water filter. After removing the composite catalyst, it was used for liquid phase testing to test the effect of different iron salt contents on the photocatalytic-self-Fenton reaction. The test results are shown in Figure 7 As shown in (D).
[0084] Figure 7 The test results of test examples 1-4 are shown in the figure, and the illustration is the data diagram of the degradation rate constant. Figure 7 As shown in (A), after 1 h of visible light irradiation, SA-TCPP produced 22.45 μmoL·g -1 ·h -1 H2O2, indicating that SA-TCPP has the potential to photocatalytically produce H2O2. x / SA-TCPP composite catalysts have significantly improved the H2O2 yield. However, when the amount exceeds a certain level, the low content of photosensitizer SA-TCPP and the excessive Ti3C2T x The shielding effect is triggered, which inhibits the absorption of light and the transfer of carriers, thereby reducing the amount of H2O2 generated. x The highest yield of the SA-TCPP composite catalyst (247.3 μmoL·g -1 ·h -1 ) are SA-TCPP and Ti3C2T x 11 and 21 times. Figure 7 As shown in (B), when the pH value is adjusted to 3, after 100 minutes of illumination, the degradation efficiency of 2,4-dichlorophenol can reach 92.9%, and the degradation rate constant can reach 0.0309 min -1 When the pH value was adjusted to 5 and 6.5, the degradation efficiency was increased to 99.7%, and the degradation rate was higher when the pH value was closer to neutral. However, when the pH value was adjusted to 8.5, the degradation rate was reduced to 60.8% because SA-TCPP was easily dissolved in an alkaline environment and the supramolecular structure was destroyed. Ti3C2T x When the SA-TCPP composite catalyst was used to degrade 2,4-dichlorophenol solution in the photocatalytic-self-Fenton system, since its original pH value was around 5 and was less affected by pH under acidic conditions, the pH was not deliberately adjusted in the subsequent experiments for degradation reaction. Figure 7 As shown in (C), after 100 min of illumination, the degradation efficiency of added Fe(III) was 99.7%, slightly higher than the degradation rate of added Fe(II) (91.3%), which is attributed to the fact that Fe(III) can consume part of the photogenerated electrons (e - ), promoting the migration and separation of photogenerated carriers, thereby generating more holes (h + ) is released and participates in the oxidation reaction. Therefore, the iron salt is preferably added with Fe(III). Finally, the dosage of the iron salt was optimized in this experiment, such as Figure 7 As shown in (D), when the amount of Fe(III) increases from 2 mg to 4 mg, the degradation efficiency of 2,4-dichlorophenol increases from 90.7% to 99.8%; however, when it is further increased to 6 mg, the excessive Fe(III) will cause the transmittance of the system to decrease, thereby reducing the degradation efficiency to 87.9%. Therefore, the dosage of Fe(III) added to the system is preferably 4 mg.
[0085] Test Example 5
[0086] The photocatalyst Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x / SA-TCPP composite catalyst is used for photocatalytic-self-Fenton water treatment, and the photocatalytic-self-Fenton degradation activity test is carried out. The test method is:
[0087] 10 mg of photocatalyst was added to 50 mL of 2,4-dichlorophenol solution (10 mg / L) and stirred in the dark for 20 min. Then 4 mg of Fe2(SO4)3 was added to the reaction system (pH value was about 5), and the light was turned on for 100 min. Oxygen was continuously introduced during the reaction. 2 mL of the sample was taken every 20 min, centrifuged and filtered through a 0.22 μm water filter head, and the photocatalyst was removed for liquid phase testing.
[0088] Figure 8 Based on Ti3C2T x Mechanism diagram of the photocatalytic self-Fenton water treatment of SA-TCPP composite catalyst. Due to the π-π stacking effect, SA-TCPP was successfully attached to the two-dimensional Ti3C2T x The Ti3C2T nanosheets with excellent photocatalytic H2O2 production activity and organic pollutant degradation effect were prepared. x / SA-TCPP composite catalyst. SA-TCPP is excited by visible light to generate photogenerated - Migrate across the forbidden band to the conduction band and leave photogenerated H + The charge delocalization effect of the π-electron conjugated structure effectively promotes the separation of photogenerated carriers and further accelerates the photogenerated electrons. - Ti3C2T x Surface transport. Due to Ti3C2T x There are unsaturated Ti 3d orbitals in the ionomer, which can adsorb dissolved oxygen in water through the pseudo-alloy effect and electron-donating defects. Then, the adsorbed O2 molecules are transferred to the photogenerated - Activated to generate superoxide anion free radical (·O2 - ), O2 - Go one step further with e - The reaction generates H2O2; the self-Fenton reaction is initiated by adding Fe(Ⅲ), and the added Fe(Ⅲ) consumes the photogenerated e on the surface of the composite material. - is reduced to Fe(Ⅱ), and then Fe(Ⅱ) reacts with Ti3C2T x / SA-TCPP composite catalyst in situ generates H2O2 to generate ·OH; due to the consumption of photogenerated e - At the same time, more photogenerated H + Therefore, in h + Under the combined action of and OH, Ti3C2T x / SA-TCPP composite catalyst-photocatalysis-self-Fenton system can achieve a significant improvement in catalytic performance and ultimately completely degrade and mineralize organic matter into CO2 and H2O.
[0089] Test Example 6
[0090] Photocatalyst Ti3C2T x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x / SA-TCPP composite catalyst was tested for photocatalytic degradation activity, the test method was:
[0091] 10 mg of photocatalyst was added to 50 mL of 2,4-dichlorophenol solution (10 mg / L) and stirred in the dark for 20 min. The light was turned on for 100 min, and oxygen was continuously introduced during the reaction. 2 mL of the sample was taken every 20 min, centrifuged and filtered through a 0.22 μm water filter to remove the photocatalyst for liquid phase testing.
[0092] The test results of test case 5 and test case 6 are as follows Fig. 9 As shown in the photocatalytic reaction, 2,4-dichlorophenol was x Nanosheets, SA-TCPP and Ti3C2T prepared in Example 1 x / SA-TCPP composite catalyst) had poor degradation activity, and the apparent reaction rate constants (k) were 0.0012min -1 、0.0014min -1 and 0.0022min -1 However, after the addition of Fe(Ⅲ) to construct the photocatalytic-self-Fenton system, the degradation performance of the three photocatalysts was improved. It is particularly noteworthy that Ti3C2T x The k value of the / SA-TCPP composite catalyst increased significantly to 0.0531min -1 , which is 24.47 times that of the photocatalytic system; therefore, compared with the photocatalytic technology, the photocatalytic-self-Fenton system may have a better degradation effect because it produces more strongly oxidizing ·OH.
[0093] Test Example 7
[0094] The degradation activity of the Fenton system was tested using H2O2 at different concentrations. The test method was as follows:
[0095] H2O2 was added to 50 mL of 2,4-dichlorophenol solution (10 mg / L) to set the concentration to 25 M, 50 M and 100 M, and stirred in the dark for 20 min. Then 5.60 mg of FeSO4 was added to initiate the Fenton reaction, and 2 mL was sampled every 20 min, centrifuged and filtered through a 0.22 μm water filter, and used for liquid phase testing after removing the photocatalyst.
[0096] The test results of test case 5 and test case 7 are as follows: Fig.10 As shown, when 25M H2O2 was added to the Fenton system, a degradation rate of 19.99% was obtained within 20 min. When the amount of H2O2 added was increased to 100M, the degradation rate increased to 82.32%. The k value of photocatalytic self-Fenton was 0.0531min -1, which is 2.38 times that of Fenton degradation when 100M H2O2 is added. This is attributed to the fact that the added H2O2 in the Fenton system cannot react with Fe(Ⅱ) in time, resulting in a large amount of ineffective decomposition of H2O2 and low utilization rate.
[0097] Test Case 8
[0098] The Ti3C2T prepared in Example 1 x The / SA-TCPP composite catalyst was used for photocatalytic-self-Fenton water treatment. The degradation performance of 2,4-dichlorophenol after adding different active species capture agents to the 2,4-dichlorophenol solution was tested. The photocatalytic-self-Fenton degradation activity test was carried out. The test method was basically the same as that of Test Example 5, except that different active species capture agents were added to the 2,4-dichlorophenol solution (the concentration after addition was 1 mmol / L), formic acid (FA), isopropyl alcohol (IPA) and p-benzoquinone (p-BQ) were used as photogenerated holes (h + ), hydroxyl radical (·OH) and superoxide anion radical (·O2 - ) to explore Ti3C2T x / SA-TCPP composite catalyst is the main active substance in the photocatalytic process.
[0099] The test results are as follows Fig.11 As shown, Ti3C2T without adding scavenger x The degradation effect of / SA-TCPP composite catalyst is remarkable. When the scavenger is added to the reaction system, it has a great influence on the degradation activity of 2,4-dichlorophenol. - and h + All are based on Ti3C2T x Photocatalysis of SA-TCPP composite catalyst - the main active substance in self-Fenton water treatment process.
[0100] Test Example 9
[0101] In order to investigate the Ti3C2T prepared in Example 1 x / SA-TCPP composite catalyst recyclability, three recycling experiments were set up to regenerate Ti3C2T x / SA-TCPP composite catalyst was used for photocatalytic-self-Fenton water treatment (Test Example 5) to investigate the effect of cyclic regeneration on the degradation of 2,4-dichlorophenol. After each cyclic regeneration, the catalyst was collected by centrifugation, fully washed with deionized water, and vacuum dried at 60°C to constant weight before continuing the next cyclic experiment. The test results are as follows Fig.12 As shown, after three consecutive cycles of regeneration experiments, the catalytic degradation rate is still close to 80%, indicating that the system has good stability.
[0102] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A Ti3C2T x The preparation method of nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst is characterized in that: The following steps are involved: (1) dissolving tetrakis(4-carboxyphenyl)porphyrin in an alkaline solution, and then adding an acid solution to adjust the pH value to neutral, thereby obtaining a self-assembled tetrakis(4-carboxyphenyl)porphyrin dispersion; (2) mixing the self-assembled tetrakis(4-carboxyphenyl)porphyrin dispersion and Ti3C2T x The dispersions are mixed to obtain the Ti3C2T x Nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst.
2. The preparation method according to claim 1, characterized in that: In step (2), the Ti3C2T x Ti3C2T in dispersion x The concentration of the nanosheets was 2-8 mg / mL.
3. The preparation method according to claim 2, characterized in that: The tetrakis(4-carboxyphenyl)porphyrin described in step (1) and the Ti3C2T4 described in step (2) x The mass ratio of nanosheets is 1:(0.2-0.8).
4. Ti3C2T obtained by the preparation method according to any one of claims 1 to 3 x Nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst.
5. Ti3C2T as claimed in claim 4 x Application of nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst in photocatalytic-self-Fenton water treatment.
6. The use according to claim 5, characterized in that: The photocatalytic-self-Fenton water treatment method comprises the following steps: adding Ti3C2T x The nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst was added with iron salt to construct a photocatalytic-self-Fenton system, which was then placed under a light source for irradiation and continuous ventilation to keep the solution in an oxygen-saturated state.
7. The use according to claim 6, characterized in that: The organic pollutant is selected from one or more of 2,4-dichlorophenol, phenol, bisphenol F and carbamazepine.
8. The use according to claim 6, characterized in that: The Ti3C2T x The mass ratio of the nanosheet / self-assembled tetrakis(4-carboxyphenyl)porphyrin composite catalyst to the iron salt is 1:(0.2-0.6).
9. The use according to claim 6, characterized in that: The iron salt is ferric sulfate and / or ferrous sulfate.
10. The use according to claim 6, characterized in that: The pH value of the photocatalytic-self-Fenton system is 3-8.5.
Citation Information
Patent Citations
Self-assembled tetra (4-carboxyphenyl) porphyrin / oxygen-doped carbon nitride nanosheet heterojunction photocatalyst as well as preparation method and application thereof
CN112121854A
Cobalt-embedded nitrogen-rich porous carbon material / self-assembled nano porphyrin composite photocatalyst as well as preparation method and application thereof
CN113694963A
Method for producing hydrogen peroxide through sacrificial-agent-free photo-thermal catalysis based on porphyrinyl supramolecules
CN114477097A
Photocatalytic self-Fenton water treatment method based on graphene / self-assembled tetra (4-carboxyphenyl) porphyrin
CN117550706A